Administrative obstacles and their reflection on the physical education lesson in the elementary schools of the General Directorate of Education in Baghdad Al-Karkh II - م.د. زينب جبار محمد (physical education and sport sciences college for women/ Baghdad University, 2021)
The research problem has crystallized in the administrative and organizational neglect of the education and sports study with its classroom and extravagant activities and the administrative and technical obstacles that prevent the application of the physical education lesson in primary schools. Al-Bishri, represented by some physical education teachers in elementary schools in the General Directorate of Education in Baghdad Al-Karkh II, and the time field from (11/11/2020) until (12/28/2020). As for the spatial field, it was in some elementary schools in the General Directorate of Education in Baghdad Al-Karkh II, either Research methodology: The descriptive method of the survey method was adopted for its suitability to the nature and problem of the research. The research community was identified with (200) teachers of physical education in primary schools as they are concerned with the research topic. Sports and its maintenance and lack of prior planning for its distribution, which hinders the implementation of most programs and competitions in physical education and sports The weak coordination between the directorates of sports and scout activity and the directorates of education in following up the classroom and extracurricular activities. As for the recommendations, the necessity of coordination between the directorates of sports and scout activity and the specialist supervisors to establish sports races for the extracurricular activity and to see the process of running those races and the lessons of physical education. Increase the holding of training and development courses for physical education teachers on a regular basis, to be acquainted with all new matters related to teaching methods, and to take out the physical education lesson to keep pace with scientific progress